DIGITALIZATION OF MUSICAL ARTS LEARNING IN RUANGGURU - Putri, Dinda Maswati (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This research aims to describe the form and role of digitalization of music arts learning carried out by Ruangguru. A qualitative approach was taken as the approach used in this research. The data used is primary and secondary data in the form of interview and product presentation materials. The analysis was carried out using qualitative descriptive analysis and after that conclusions were drawn. The results of this research show that the form of digitalization of music art learning carried out by Ruangguru is that students can choose their own music teacher, can determine their learning schedule and determine the music art topics that will be discussed. Apart from that, Ruangguru also combines features for booking music classes, learning video calls and learning recordings in one centralized application and website. In the learning process, the material is divided into three levels, namely beginner, intermediate and advanced. Each level has different learning material. The higher the level, the more difficult the material becomes. However, the material has been made sequentially so that it is easy for students to understand. The role of digitalization of music arts learning at Ruangguru is that it can offer flexibility and learning is carried out centered on one Ruangguru application. Apart from that, learning can also run more focused and according to students' needs. Students can absorb learning material more easily because the material is divided into three levels with different levels of ability and difficulty.